Type I interferon signaling in SARS-CoV-2 associated neurocognitive disorder (SAND): Mapping host-virus interactions to an etiopathogenesis - Vavougios, George D.; Erausquin, Gabriel A. de; Snyder, Heather M. (Frontiers in Neurology, 2022)
Epidemiological, clinical and radiological studies have provided insight into the phenomenology and biological basis of cognitive impairment in COVID-19 survivors. Furthermore, its association with biomarkers of neuroinflammation and neurodegeneration support its case as a distinct LongCOVID syndrome with specific underlying biology. Accounting for the latter, translational studies on SARS-CoV-2’s interactions with its hosts have provided evidence on type I interferon dysregulation seen in neuroinflammatory and neurodegenerative disease. To date, studies attempting to describe this overlap have only described common mechanisms. In this manuscript, we attempt to also formulate a mechanistic model based on host-virus interactions, In this review, we discuss the molecular basis for a SARS-CoV-2 associated neurocognitive disorder (SAND) focusing on specific genes and pathways with potential mechanistic implication, several of whom have been predicted by our group. Furthermore, we formulate a hypothesis that specifically links translational evidence on interferon-responsive gene perturbations introduced by SARS-CoV-2 and known dysregulated pathways in dementia, Finally, we emphasize on the crosstalk between central and peripheral immunity via danger-associated molecular patterns, in inducing SAND’s emergence in the absence of neuroinfection. Finally, we outline targets that are both testable and druggable, and could serve in the design of future clinical and translational studies.